Development and validation of a rapid test for anaerobic inhibition and toxicity. (15th September 2015) - Astals, S.; Batstone, D.J.; Tait, S.; Jensen, P.D.
Abstract: Despite the importance of quantifying inhibitory capacity of compounds in anaerobic digestion, there is currently no well-defined method to assess it. Experimental methods in literature are frequently time-consuming and resource intensive. As a result, detailed inhibition testing rarely forms part of anaerobic digestion studies, despite the importance and utility of this information. This study develops and validates a simple and rapid inhibition test protocol, based on relative inhibition of acetoclastic methanogens. The inhibition potential of a compound is determined from the reduction in specific methanogenic activity as inhibitor concentration is increased. The method was successfully performed on two inoculums from different source environments and with both biostatic and biocidal inhibitors. Optimisation work indicated that: (i) sodium acetate is a preferred carbon source compared to acetic acid; (ii) an inoculum to acetate ratio of 5 g VS g −1 acetate is preferred, and (iii) that the inoculum concentration should be normalised to 10 g L −1  VS to reduce mass transfer problems and promote consistency. A key advantage over existing methods is that the sampling strategy has been optimised to three events over 1.5 days while effectively controlling the relative analytical error. Highlights: New method to quantify inhibition of acetoclastic methanogens. Method validated with 2 inoculums and 3 inhibitors. Methanogenic activity is determined through 3 sampling events over 1.5 days. The test can be completed 3 days after collecting the inoculum.